2014
DOI: 10.3892/etm.2014.1945
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pure yolk sac tumor in the anterior third ventricle of an adult: A case report

Abstract: A 45-year-old female patient presented with symptoms of polydipsia and polyuria, menopause, headache, gait disturbance and deteriorated mental state. Brain magnetic resonance imaging (MRI) showed an irregular mass in the anterior third ventricle. The tumor was excised using a transfrontal approach from the anterior section of the third ventricle. The histological diagnosis was of an intracranial pure yolk sac tumor. The patient underwent radiotherapy and suffered no tumor recurrence one year after the surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In most cases, the onset of YST occurs in childhood and young adulthood. In the relevant English literature, there are only 5 reported cases of YST in patients over 35 years old (Table 1) (23)(24)(25)(26)(27). Our case represents the fourth-oldest patient with adult-onset yolk sac tumor reported worldwide.…”
Section: Discussionmentioning
confidence: 86%
“…In most cases, the onset of YST occurs in childhood and young adulthood. In the relevant English literature, there are only 5 reported cases of YST in patients over 35 years old (Table 1) (23)(24)(25)(26)(27). Our case represents the fourth-oldest patient with adult-onset yolk sac tumor reported worldwide.…”
Section: Discussionmentioning
confidence: 86%
“…Serum AFP level is a common indicator for evaluating the treatment response to YSTs. [7] Studies have shown that serum AFP >1000 ng/mL at the time of diagnosis is a risk factor for subsequent [10] M 23 Pineal region No Yes No NR 2017 [11] M 17 Hypothalamic and Pineal region Yes Yes Yes Alive 2014 [12] M 2 Cerebellar vermis Yes Yes No NR 2014 [13] F 45…”
Section: Discussionmentioning
confidence: 99%
“…The majority of locations are near the midline, such as the saddle and pineal region, basal ganglia and the thalamus (24,4,12), a few may occur in the lateral ventricles, third ventricle, cerebral hemispheres or brainstem (1,19,25). The imaging diagnosis of intracranial germ cell tumors in typical regions are more clear, but in rare site are easily misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The germinomas is most common in germ cell tumors, followed by teratoma, endodermal sinus tumor and choriocarcinoma are rare (10). The majority of locations are near the midline, such as the saddle and pineal region, basal ganglia and the thalamus (24,4,12), a few may occur in the lateral ventricles, third ventricle, cerebral hemispheres or brainstem (1,19,25). On review of literature, very few case reports of yolk sac tumor have been published.…”
Section: Introductionmentioning
confidence: 99%